THE IMPORTANCE OF SOCIAL ENTREPRENEURSHIP TO THE PROCESS OF GLOBALIZATION OF THE ECONOMY AND MARKETS - Bouby Tolentino, Francisca (2015)
The objective of the present paper is to contribute to the debate that will allow us to deepen the analysis of why the separation between ethics and economic science has led us to forget the altruistic dimension of human being and consider only its selfish dimension, the same that has shaped a global economic system with problems of inequality, poverty, social exclusion and environmental disarray. The critical analysis of the various reviewed documents in relation to this debate and the resulting indicators, lead us to raise the importance of social entrepreneurship, linked to the achievement of a more fair economic system where ethics and economy are inextricably linked. Social entrepreneurship is emerging as a response to the problems that the model of global capitalism is generating to the population and to fill the vacuum of weak social policies of governments focusing on policies of deregulation and economic liberalization. Social entrepreneurship constitutes a supplementary business model to the economic or market entrepreneurship and to the existing corporate enterpreneural system, by way of acting in áreas where market enterpreneurship usually doesn’t act. Therefore, it can contribute in the improvement of the global economic system, giving shape alltogether to a more fair and efficient system.